Effect of esterified hyaluronic acid as middle ear packing in tympanoplasty for adhesive otitis media. (1st February 2018) - Deng, Rui; Fang, Yanqing; Shen, Jun; Ou, Xiong; Liuyan, Wenyi; Wan, Bin; Yuan, Yasheng; Cheng, Xiaoting; Shu, Yilai; Chen, Bing
Abstract: Objectives: The goal of this study was to evaluate the effects of middle ear packing agents (MEPA) on post-operative hearing improvement and complications after tympanoplasty in patients with adhesive otitis media (OM). Materials and methods: Patients with adhesive OM who underwent tympanoplasty surgery were enrolled in the study between January 2012 and January 2015. A total of 205 patients who received canal wall-down tympanoplasty with ossicular chain reconstruction were randomized into one of the three groups with different MEPA. Group 1 ( n = 72) received MeroGel as the MEPA, Group 2 ( n = 64) cartilage, and Group 3 ( n = 69) both. Air conduction (AC) and bone conduction (BC) thresholds at 0.5, 1, 2, and 4 kHz were measured, and air-bone gaps (ABG) were analyzed before and after the surgery for each patient. Results: Mean pre- and post-operative ABG was 30.9 dB and 17.6 dB in Group 1, 31.4 dB and 21.9 dB in Group 2, and 32.2 dB and 19.1 dB in Group 3. The ABG closure was 13.3 ± 7.5 in Group 1, 9.5 ± 5.9 in Group 2, and 13.1 ± 9.3 in Group 3. The improvement of ABG after surgery was statistically significant in all three groups ( p < .05). The ABG closure was statistically significantly smaller in Group 2 than in other two groups ( p < .05). Conclusions: Tympanoplasty using esterified hyaluronic acid (i.e. MeroGel) or cartilage as the MEPA resulted in improved hearing for patients with conductive hearing loss due to adhesive OM. Using MeroGel as the MEPA appeared to achieve a better post-operative outcome than using cartilage.